Antiaging and Antioxidant Bioactivities of Asteraceae Plant Fractions on the Cellular Functions of the Yeast Schizosaccharomyces pombe - Rika Indri Astuti; Muhammad Eka Prastya; Irmanida Batubara; Eka Budiarti; Aulia Ilmiyawati (Advances in Pharmacological and Pharmaceutical Sciences)
Research on antioxidants has been gaining worldwide attention because of their essential applications for medicinal purposes. In this study, we conducted bioprospecting of six Asteraceae plants as the source of antiaging and antioxidant agents. Water and chloroform fractions from Ageratum conyzoides L., Dichrocephala integrifolia (L.f.) Kuntze, Galinsoga parviflora (Cav.), Mikania micrantha Kunth, Sphagneticola trilobata (L.) Pruski, and Synedrella nodiflora L. were collected and assayed for their in vitro antioxidant activities and potential antiaging properties using the yeast Schizosaccharomyces pombe as the model organism. Based on the in vitro assay, the water fractions of S. trilobata showed a strong antioxidant activity. Interestingly, all treatment solutions promoted the stress tolerance phenotype of S. pombe to strong H2O2-induced oxidative stress conditions. Moreover, compared with the treatments without plant extract/fraction, all extract and fraction treatments, except the chloroform fractions of A. conyzoides, promoted yeast cell longevity. Strong induction of mitochondria activity was found following the treatments with the extracts and fractions of S. nodiflora, D. integrifolia, and M. micrantha and likely mimicked the calorie restriction-induced lifespan. Interestingly, S. nodiflora water fractions significantly upregulated the mRNA transcripts of the Pap1-mediated core environmental stress response, namely, ctt1 gene in S. pombe. These data indicated that the fractions of Asteraceae plants had potential antioxidant and antiaging activities through various cellular modulations. S. nodiflora water fraction has been shown to have antioxidant and antiaging activities in S. pombe, by modulating stress tolerance response, inducing mitochondrial activity, and increasing the ctt1 gene expression. Compounds analysis identified that S. nodiflora water fraction contained some primarily compounds including oxyphyllacinol, valine, and sugiol.